Inovasi E-Gelang Sebagai Alat Deteksi Dini Untuk Meminimalisasi Penyebaran Covid-19 - Sukma Rahmawati; Eko Purwanto (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2020)
In 2020, there was a disease that horrified the world. Where pneumonia resembles, this disease originates from a virus similar to coronavirus and is called Covid-19. Covid-19 was received from Wuhan, China. Spread throughout the world and mostly for locking to break the Covid-19 distribution chain. Therefore, this paper was made to submit opinions about ideas put forward on the e-bracelet system as a Covid-19 early detection device connected to a smartphone application to see the results of its detection testing. Reference to early detection of Covid-19 presence of body temperature sensors, distance and heart rate. The method of use of this paper is the method of library study and the existence of a design system called the prototyping method. Literature study is carried out by gathering information relevant to topics that are the object of research from books, scientific papers, theses, dissertations, and journals, while the prototype used is development before leading to actual large / scale production. The results will be obtained is proof of our acceptance, our heart rate is not normal, can know our distance from the crowd is not controlled. And this e-bracelet is designed so that when 2 or more e-bracelet at the same place when it is turned on, the continuity will be notify on the application interface handphone. Mild symptoms of Covid-19 are, dry throat, sudden shortness of breath, loss of acuity of smell. The way to avoid this is by diligently washing hands, carrying hands, adhering to health protocols. The idea of converting this bracelet as an early detection of Covid-19 symptoms which can measure body temperature, distance, and heart rate as a reference to support from the self that is issued.